EXTENT OF UTILIZATION OF ICT- BASED FACILITIES IN KINDERGARTEN READING INSTRUCTION IN MARSHALL DISTRICT, MARGIBI COUNTY, LIBERIA - Obidike, Ngozi Diwunma; Mulbah, Hannah Garmai (Journal of Early Childhood and Primary Education, 2025)
This study examined the extent of utilization of ICT – Based facilities in kindergarten reading instruction within Marshall District, Liberia. Two research questions and two hypotheses were posted to guide the study. Descriptive survey research design was adopted for the study. The population of the study comprised 348 Early Childhood teachers in 115 ECE schools in rural and urban areas in Marshall District, Margibi County. All the 348 ECE teachers were used for the study. However, only 174 respondents properly filled and returned the questionnaire. Data were collected using a self-structured instrument titled Extent of Utilization of ICT-Based Facilities in Kindergarten Reading Instruction Questionnaire (EUIBSKRIQ). The instrument was validated by three experts in the field of Education. The reliability coefficients were obtained using the Cronbach Alpha method which yielded 0.90 and 0.73 confirming strong internal consistency of the instrument. Descriptive statistics, including mean and standard deviation, were used for analysis, while the hypotheses were tested at 0.05 significance level using t-test statistics. Findings revealed that ICT facilities are used to a low extent, with teachers relying mainly on basic tools such as printers and literacy apps, while advanced technologies like computers, smartphones, and internet services remain underutilized (grand mean = 2.27). Significant disparities were observed between urban and rural schools, reflecting inequities in infrastructure and access. Despite these limitations, teachers expressed strong confidence in ICT’s effectiveness for enhancing phonics, vocabulary, and comprehension (grand mean = 3.13), indicating that external constraints rather than resistance hinder integration. Years of teaching experience also influenced ICT use, with experienced teachers adapting tools more effectively. The study recommends strengthening infrastructure, ensuring equitable resource distribution, and providing continuous training and mentorship to align teachers’ positive perceptions with practical opportunities for ICT integration in early childhood classrooms.
Keywords: ICT integration; Kindergarten reading instruction; Early childhood education; Urban–rural disparities; educational technology utilization